Польша в жизни и творчестве Наталии Горбаневской - Rudziewicz, Irena (Acta Polono-Ruthenica, 2018)
In the text presented were various forms of the Russian poetess Natalya Gorbanevskaya’s connections with Polish culture and literature, political and civil right activists, editorial boards of magazines in emigration and in Poland. Attention was also paid to Gorbanevskaya’s translations of Polish poets representing various age groups into the Russian language.